Regulatory Impact Analysis (RIA) terhadap Implementasi Pilar Smart Environment dalam Masterplan Smart City Kota Surabaya - Irla Hadratan Iman irla; Nur Aini; Risca Amelia; Suryani; Fajar Apriani (Social Science Academic, 2026)
Digital transformation in urban governance has encouraged local governments in Indonesia to adopt the Smart City concept as a sustainable development strategy. Surabaya City is one of the regions actively implementing the Smart City concept through Mayor Decree Number 100.3.3.3/282/436.1.2/2023 concerning the Surabaya Smart City Masterplan 2023–2026. One of the main pillars within this policy is Smart Environment, which focuses on improving environmental quality through information technology utilization, sustainable resource management, and community participation. This study aims to analyze the regulatory impacts of Smart Environment implementation on urban environmental management performance in Surabaya using the Regulatory Impact Analysis (RIA) approach. The research employs a qualitative descriptive method using regulatory documents, government reports, and scientific literature as data sources. The findings indicate that Smart Environment implementation has positively contributed to environmental governance, waste management systems, green open spaces, and environmental awareness. Nevertheless, challenges remain in terms of digital literacy disparities, institutional integration, and environmental technology infrastructure. Strengthening institutional coordination and human resource capacity is therefore essential to optimize Smart Environment implementation and support sustainable urban development.